Antimicrobial Properties of Distichochlamys citrea M.F. Newman Rhizome n‐Hexane Extract against Streptococcus pyogenes: Experimental Evidences and Computational Screening. Issue 17 (3rd May 2022) - Van Hue, Nguyen; Cuong, To Dao; Quy, Phan Tu; Bui, Thanh Q.; Hai, Nguyen Thi Thanh; Triet, Nguyen Thanh; Thanh, Doan Duy; Nhi, Nguyen Thanh To; Thai, Nguyen Minh; Van Chen, Tran; Nhung, Nguyen Thi Ai
Abstract: Distichochlamys citrea, an endemic plant species found only in Vietnam, traditionally known effective for internal inflammation and infection, thus considered as a promising natural antibiotic source. A variety of experimental‐computational methodologies were utilised. Gas chromatography‐mass spectrometry reveals twenty‐one bioactive components (C1 ‐C21 ) is found in the n ‐hexan extract. Bioassays indicate its total antibiotic activity of high significance against Streptococcus pyogenes (IZD 14±2.0 mm; MIC value of 156.25 μg.mL −1 ). Docking simulation predicts C17 (DS −12.9 kcal.mol −1 ; RMSD 1.34 Å)>C14 (DS −12.3 kcal.mol −1 ; RMSD 1.58 Å)>C16 (DS −12.0 kcal.mol −1 ; RMSD 1.30 Å) as the most effective inhibitors towards S‐ribosylhomocysteine lyase structure (UniProtKB: P0C0C7). Quantitative structure‐activity relationships suggest all the compounds are predicted with high biocompatibility in reference for oral drug development, and specifiy C1 ‐C21 especially safe for use in vertebrates. The results preliminarily confirm the significant antibiotic activity of Distichochlamys citrea and encourage further in‐depth experiments in order to harness its pharmacological potentiality. Abstract : Distichochlamys citrea is an endemic plant species found only in Vietnam, known by folk medicine as a natural antibiotic source. Experimental evidences and computational validation on bioactivity of Distichochlamys citrea M.F. Newman rhizome n ‐hexane extract against Streptococcus pyogenes were carried out. Experiments found twenty‐one bioactive components in the n ‐hexane extract, which altogether exhibits an overall antibiotic activity of significance against the bacterium; Computations suggested a mechanism based on inhibition of S‐ribosylhomocysteine lyase structure. Its biocompatibility and pharmacology were also predicted.